The decision [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Prairie state friends, 2015)
Jonah Miller was left at the altar by the love of his life. He hopes he left heartbreak behind when he moves from Pennsylvania to Illinois, settling into a new Amish community as a buggy maker. He starts to court Elaine Schock, who works with her grandmother to host dinners in their home for tourists. But when her grandfather suddenly dies and her grandmother -- her only living relative -- slips into dementia, Elaine ignores her growing love for Jonah and sets him free to look for love elsewhere. Jonah is sure he won't find a love a third time. Is God calling him to remain single, or does he have a different plan for the lonely Amish man?